A cake making strategy to prepare reduced graphene oxide wrapped plant fiber sponges for high-efficiency solar steam generation. Issue 30 (18th July 2018) - Chen, Tingjie; Wang, Sha; Wu, Zhenzeng; Wang, Xiaodong (Alice); Peng, Jian; Wu, Binghui; Cui, Jingqin; Fang, Xiaoliang; Xie, Yongqun; Zheng, Nanfeng
Abstract : A cake making strategy is developed to prepare reduced graphene oxide wrapped plant fiber sponges for high-efficiency solar steam generation. Abstract : A facile method inspired by the cake making process is developed to fabricate reduced graphene oxide wrapped plant fiber sponges (PFS@rGO) through in situ coating and foaming. This method avoids the use of energy-intensive equipment for molding and drying, and hence has great potential in the production of large-sized rGO sponges. With a highly porous framework, good mechanical properties, efficient solar absorption, and low thermal conductivity, the as-fabricated hydrophilic and light-weight PFS@rGO readily floats on seawater and generates water vapor with a solar thermal conversion efficiency of 88.8% under 1 sun illumination.